2010
DOI: 10.1080/01904160903470430
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters of Canola as Affected by Nitrogen and Sulfur Fertilization

Abstract: to evaluate the effects of nitrogen (N) and sulfur (S) levels and their methods of application on quality parameters of canola . Four levels of S (0, 20, 40, and 60 kg ha −1 ) and three levels of N (80, 120, and 160 kg ha −1 ) and a control treatment (with both nutrients at zero level) were applied as a sole dose at sowing, in two split applications (half each at sowing and leaf rosette stages) and three split applications (one third each at sowing, leaf rosette stage, and early flowering). Large increases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
5
9
1
1
Order By: Relevance
“…The number of per plant had significantly affected by both nitrogen levels and application methods, while the interaction affect was non-significant. The finding are correlated to [9] who stated the nitrogen enhance the vegetative and reproductive growth of canola. Days to first flowering response was significant in cases of nitrogen levels and application methods, while the effect was non-significantly in case of interaction.…”
Section: Discussionsupporting
confidence: 74%
“…The number of per plant had significantly affected by both nitrogen levels and application methods, while the interaction affect was non-significant. The finding are correlated to [9] who stated the nitrogen enhance the vegetative and reproductive growth of canola. Days to first flowering response was significant in cases of nitrogen levels and application methods, while the effect was non-significantly in case of interaction.…”
Section: Discussionsupporting
confidence: 74%
“…Treatment (T-3) (40S + 100N) resulted in maximum contents on protein, N. and S. Authors concluded that a balanced N and S supply should be maintained for both quantity and quality of oil of Brassica genotypes. Jan et al [ 75 ] evaluated the effects of N and S levels and their methods of application on quality parameters of canola ( B. napus L. cv. “Bulbul-98”) taking into account four levels of S (0, 20, 40, and 60 kg ha −1 ) and three levels of N (80, 120, and 160 kg ha −1 ) and a control treatment (with both nutrients at zero level) applied either as a sole dose at sowing, in two split applications (half each at sowing and leaf rosette stages) or three split applications (one third each at sowing, leaf rosette stage, and early flowering).…”
Section: Growth Photosynthetic Functions and Seed/oil Yield And Qmentioning
confidence: 99%
“…Plants in 2013 produced higher amounts of GSs than that in 2012, which corresponded to the higher amount of background S availability in soil in 2013. Sulphur application increased the total amount of GSs in turnip rape (Kim et al, 2002), rapeseed ( Jan et al, 2010;Asare and Scarisbrick, 1995;Josefsson, 1970;Šiaudinis and Butkutė, 2013;Withers and O'Donnell, 1994), and broccoli (Rangkadilok et al, 2004;Schonhof et al, 2007;Vallejo et al, 2003;Zhao et al, 1997). The mean monthly temperatures during the plant reproductive development stage ( July and August) at Canning in 2012 and 2013 were similar, so it was difficult to determine the temperature effects on the GS formation in the present study.…”
Section: Discussionmentioning
confidence: 82%